Different groups of ground‐dwelling spiders share similar trophic niches in temperate forests. (23rd July 2020) - Zuev, Andrey; Heidemann, Kerstin; Leonov, Vladislav; Schaefer, Ina; Scheu, Stefan; Tanasevitch, Andrei; Tiunov, Alexei; Tsurikov, Sergey; Potapov, Anton
Abstract : Generalistic interactions between predator and prey may vary with ecosystem type, predator traits, and prey traits, but the interplay of these factors has not been assessed in ground food webs. We investigated trophic interactions of ground‐dwelling spiders across eight forests in European Russia associated with body size, hunting strategy, microhabitat specialization, potential prey type, potential prey population density, and forest type (coniferous vs. broadleaved). We analyzed 128 individual spiders, including juveniles, all identified to the family level with two complementary methods: molecular gut content analysis, and stable isotope analysis of carbon and nitrogen. The results suggest that feeding frequency of spiders is affected by predator body size and by selection of certain prey type. Stable isotope analysis showed similar trophic niches among spider families, varying moderately with forest type. Larger spiders had higher Δ 13 C values than smaller ones, but similar Δ 15 N values, suggesting that different size classes of spiders belong to different food chains. Results based on stable isotope and molecular gut content analyses were weakly linked, indicating them targeting different trophic niche dimensions. At least for the group‐level interactions, family identity and hunting strategy of predator has little predictive power while predator body size and prey traits affected trophic niche dimensions calling for future studies in this direction. Large spiders feed more and rely on different basal resources than small spiders, suggesting that including small species and juveniles provides a more comprehensive picture of food web organization. Abstract : Stable isotope composition and gut content DNA were analysed together in 128 individual spiders in four coniferous and four broadleaved forests in European Russia. Feeding frequency was affected by predator body size and certain prey types were preferred, while forest type, taxonomy, and hunting strategy had moderate effect on feeding of co‐occurring spiders. Larger spiders had higher 13C enrichment (resources) than smaller ones, but similar 15 N enrichment (trophic level), suggesting that different size classes of spiders belong to different food chains.